The Politicization Of The Holy God And Its Impact On The Social System In Mesopotamia - حيدر, هدى علي; مجيد, هند فائز (Al-Adab Journal, 2019)
The idea of ​​religion begins with the beginning of man, and there is no influential idea in societies such as religion, whose creation has been linked to human life since ancient times. Like other religions, it urged the Mesopotamian religion on the moral side of the individual and the obligation to be committed to the rituals of worship , Political thought is an old human societies, as the knowledge of politics and the beginning of its practices were associated with the existence of this society, in order to live under the rules governing its various affairs, and the relationship seems clear between religion and political thought in Mesopotamia, The archaeological remnants, whether written or carved, and this relationship was so strong that we see that religious thought conceals the political thought in many times between the sides, so the political thought in Mesopotamia was born of the womb of religion and remained associated with it throughout its historical stages, so we did not see The rise of the Rafidian political thought to the level of political theory, and the upper hand of the religion has gone to the path it wishes, ignoring its social system and the problem of collective consciousness subjected to its theocratic methodology.